2013
DOI: 10.1136/oemed-2012-101184
|View full text |Cite
|
Sign up to set email alerts
|

The impact of job stress due to the lack of organisational support on occupational injury

Abstract: This prospective study found evidence of an association between the LOS and the incidence of occupational injuries in women, with potential implications for the prevention of accidents at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…Work-related factors that have been considered include a variety of physical and psychosocial working conditions. Several studies confirmed that dangerous work conditions, job stress, and high physical and mental workload were associated with work accidents and absence [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 95%
“…Work-related factors that have been considered include a variety of physical and psychosocial working conditions. Several studies confirmed that dangerous work conditions, job stress, and high physical and mental workload were associated with work accidents and absence [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 95%
“…Recently, a 1-year follow-up prospective study in Spain was conducted to investigate any association between job stress related to organisational support and occupational injuries 21. Lack of organisational support was evaluated by questionnaires and then estimated by index, severity and frequency; all were positively correlated with the risk of occupational injury.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of job stress. Recent studies have shown that occupational injury is associated with excessive workload, high cognitive demands and low job satisfaction, high intragroup conflict, job insecurity,19 low decision latitude, conflicts with the supervisor or colleagues,20 lack of organisational support,21 poor physical environment, unfair reward and treatment,22 verbal abuse and low predictability,23 and organisational injustice 24…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, some studies found that job stress and demanding physical and mental workloads increase the risk for occupational accidents and injuries. 10,11 Hazardous worksite conditions (e.g. loud noise, vibration, extreme temperatures) and a lack of protective equipment and training are other well-documented factors that contribute to injury.…”
mentioning
confidence: 99%